The International Energy Agency's Role in Supporting the Sustainability of Renewable Energy Supply in Indonesia - Nurmasari Situmeang; Sindy Yulia Putri; Shafa Qisisina Desbrantoro; Yosua Saut Marulitua Gultom; Syifa Aprilia Putri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Indonesia, as a country with abundant natural resources, faces serious challenges related to the use of non-renewable natural resources such as petroleum. Negative environmental impacts and the risk of depletion of these resources have triggered the need for a transition to renewable energy. We use an inductive qualitative method through document research as data collection. Given the International Energy Agency's (IEA) role in supporting national energy sustainability and reviewing Indonesia's energy policies, a pertinent question arises regarding its role in Indonesia. This study aims to analyze the concrete role of the International Energy Agency (IEA) in supporting the sustainability of renewable energy supply in Indonesia with reference to SDG 7. This study finds that the role of the IEA in striving for a renewable energy transition in Indonesia centres on providing analysis of the potential and challenges as well as policy recommendations to direct the government in developing strategies for implementing renewable energy. The IEA also facilitates international cooperation, technology transfer, and investment in the renewable energy sector. Indonesia is committed to achieving the targets of Sustainable Development Goal (SDG) 7, which focuses on universal access to affordable, clean, and sustainable energy. Cooperation with the IEA will continue to be key in achieving this goal, especially to achieve the net-zero emissions target by 2060 and ensure the availability of a sustainable renewable energy supply.